Changes in gene expression in the larval gut of Ostrinia nubilalis in response to Bacillus thuringiensis Cry1Ab protoxin ingestion - Yao, Jianxiu; Buschman, Lawrent L.; Lu, Nanyan; Khajuria, Chitvan; Zhu, Kun Yan (My University, 2014)
We developed a microarray based on 2895 unique transcripts assembled from 15,000 cDNA sequences from the European corn borer (Ostrinia nubilalis) larval gut. This microarray was used to monitor gene expression in early third-instar larvae of Bacillus thuringiensis (Bt)-susceptible O. nubilalis after 6 h feeding on diet, with or without the Bt Cry1Ab protoxin. We identified 174 transcripts, for which the expression was changed more than two-fold in the gut of the larvae fed Cry1Ab protoxin (p < 0.05), representing 80 down-regulated and 94 up-regulated transcripts. Among 174 differentially expressed transcripts, 13 transcripts putatively encode proteins that are potentially involved in Bt toxicity, and these transcripts include eight serine proteases, three aminopeptidases, one alkaline phosphatase, and one cadherin. The expressions of trypsin-like protease and three aminopeptidase transcripts were variable, but two potential Bt-binding proteins, alkaline phosphatase and cadherin were consistently up-regulated in larvae fed Cry1Ab protoxin. The significantly up and down-regulated transcripts may be involved in Cry1Ab toxicity by activation, degradation, toxin binding, and other related cellular responses. This study is a preliminary survey of Cry1Ab protoxin-induced transcriptional responses in O. nubilalis gut and our results are expected to help with further studies on Bt toxin-insect interactions at the molecular level.
Citation: Yao, Jianxiu, Lawrent Buschman, Nanyan Lu, Chitvan Khajuria, and Kun Zhu. (2014).Changes in Gene Expression in the Larval Gut of Ostrinia Nubilalis in Response to Bacillus Thuringiensis Cry1Ab Protoxin Ingestion. Toxins 6 (4): 1274–94. https://doi.org/10.3390/toxins6041274.
Keywords: Bacillus thuringiensis; European corn borer; Ostrinia nubilalis; Cry1Ab protoxin; Microarray; Transcriptional response